PENGEMBANGAN EVALUASI FORMATIF PADA SISWA KELAS 5 SDN PORIS PELAWAD 5 - Rosita, Ria; Safitri, Santi; Magdalena, Ina (Transpublika Publisher, 2023)
This article is a theoretical study of the development of formative evaluation in 5th grade students at SDN Poris Pelawad 5. This study aims to find out and describe empirically about: Aspects, techniques and procedures for class assessment carried out by teachers and students in 5th grade at SDN Poris Pelawad 5. Educators' use of assessment tools is crucial to the success of their lessons. Teachers' abilities to manage their classrooms effectively and to select instructional strategies, media, materials, etc. that will inspire their pupils to learn can be enhanced through evaluation. And also, teachers can gauge their pupils' progress through evaluation. Hence, teachers need to ensure that assessment procedures are carried out effectively. Assessment, assessment methods, and assessment procedures are all part of the Scriven-created formative evaluation paradigm used in this qualitative study. The ADDIE model is an all-purpose instructional design framework that may be applied to both face-to-face learning settings and online learning environments. Instructional resources with a detailed explanation of the material's strengths and weaknesses, used both to guide instruction and assess progress toward learning outcomes are an integral part of any successful educational program.